Between the First and the Second Serbia: On the Political and Class Dimension of Hip-Hop Subculture in Serbia - Kovačević, Predrag S. (Sociološki pregled, 2018)
This paper tackles the phenomenon of hip-hop subculture in Serbia. The goal is to understand its development and to map out its class dimensions and political impulses. The analysis is grounded in cultural studies (cf. Hall, 1980). Hip-hop lyrics and symbolism of the hip-hop style are analyzed with a focus on political and class dimensions. The development of hip-hop subculture is divided into two phases. First, during the 1990s, the hip-hop subculture in the Serbian context was in the search for its local identity as a style that originated within the working-class but had its frst representatives in Serbia among the middle-class youth. Hip-hop’s dialogue with the dizel culture during this period is indicative of this quest for identity. In the second phase, afer 2000, hip-hop fnds its place in the Serbian society by grounding itself in the working-class and establishing itself as the heir of the dizel subculture of the nineties (Papović and Pejović 2016). It also undergoes internal divisions producing an elitist wing further subdivided into a liberal and conservative part, and an anti-elitist wing with a chaotic political character hosting both radically lefwing and extreme right sentiments. Keywords: hip-hop, subculture, elite, class, politics, transition